Critical thinking : a user's manual - Jackson, Debra; Newberry, Paul A. (Wadsworth Cengage Learning, 2012)
Offers a skill-based approach to critical thinking that provides step-by-step tools for learning to evaluate arguments. This title offers multiple opportunities for different kinds of practice and options for appealing to different learning styles